2011
DOI: 10.3892/ol.2011.541
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the FAS and FASL genes and risk of breast cancer

Abstract: Abstract. FAS and its ligand FASL are crucial in apoptotic cell death. Loss of FAS and gain of aberrant FASL expression are common features of malignant transformation. This study was designed to investigate whether the functional polymorphisms of FAS -1377G/A (rs2234767) and FASL -844T/C (rs763110) affect the risk of developing breast cancer. Genotypes were analyzed by a polymerase chain reaction-restriction fragment length polymorphism assay in 436 breast cancer patients and 496 healthy controls. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Accordingly,they become more sensitive to apoptosis when they interact with cells that express the FasL on their surface (Nagata et al, 1995;Ehrenschwender et al, 2009). Evidence for this mechanism of tumor immune privilege has been provided for several cancers (Zhou et al, 2006;Wu et al, 2010;Gomes et al, 2011;Cai et al, 2012;Tian et al, 2012;Wang et al, 2012) that have been shown to express FasL, including skin, lung, breast, and cervical cancers, gastric cancer. To date, the molecular events underlying the role of Fas/FasL in the progression to oral carcinoma are poorly understood (Chen et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly,they become more sensitive to apoptosis when they interact with cells that express the FasL on their surface (Nagata et al, 1995;Ehrenschwender et al, 2009). Evidence for this mechanism of tumor immune privilege has been provided for several cancers (Zhou et al, 2006;Wu et al, 2010;Gomes et al, 2011;Cai et al, 2012;Tian et al, 2012;Wang et al, 2012) that have been shown to express FasL, including skin, lung, breast, and cervical cancers, gastric cancer. To date, the molecular events underlying the role of Fas/FasL in the progression to oral carcinoma are poorly understood (Chen et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…FasL polymorphism was associated with the increased risk of neuroblastoma [21], laryngeal and hypopharyngeal squamous cell cancer [23], epithelial ovarian cancer [24], breast cancer [26], and gastric cardiac adenocarcinoma [46]. Also FasL polymorphism was a low risk factor for oral cancer [25], pancreatic cancer [30], and breast cancer [19,32].…”
Section: Discussionmentioning
confidence: 95%
“…Recently, SNPs of the Fas or FasL genes have been shown to be associated with an increased risk of several cancers [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] and with the prognosis of several cancers [34][35][36][37][38][39][40]. However, the association between thyroid cancer and SNPs of the Fas and FasL genes is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…The mFasL.2 allotype exhibits 9-fold-higher binding affinity to the Fas receptor and cytotoxic activity against Fas ϩ target cells than mFasL.1. Polymorphisms in the FasL gene have also been found in humans and have been associated with increased risk of some cancers (18)(19)(20). However, it is not known how these FasL polymorphisms may influence the immune response and susceptibility to infection in humans.…”
mentioning
confidence: 99%